11B NMR/MRI Sensing of Copper(II) Ions In Vitro by the Decomposition of a Hybrid Compound of a nido‐o‐Carborane and a Metal Chelator. Issue 20 (10th June 2016) - Tanaka, Tomohiro; Araki, Rikita; Saido, Takaomi; Abe, Ryo; Aoki, Shin
Abstract : Cu 2+ is closely correlated with certain types of physiological and pathological events. Therefore, the development of a noninvasive methodology for detecting Cu 2+ is important for understanding its biological role and relationship with disease. Herein, we report on the development of a Cu 2+ ‐specific 11 B NMR/MRI probe that contains a chelator unit, TriMEDA. The method is based on the rapid complete deboronation of nido ‐ o ‐carborane by Cu 2+ under physiological conditions. Abstract : A hybrid molecule made up of a nido ‐ o ‐carborane and a metal chelator decomposes rapidly in the presence of Cu 2+ under mild conditions. This probe is useful for the 11 B NMR/MRI sensing of Cu 2+ in vitro.